2012
DOI: 10.1177/1756287212459549
|View full text |Cite
|
Sign up to set email alerts
|

Experience with imidafenacin in the management of overactive bladder disorder

Abstract: Overactive bladder (OAB) is a chronic syndrome defined by symptoms of urinary urgency with no underlying medical causes. First-line treatment of OAB comprises fluid intake advice and bladder training, supplemented by anticholinergic drugs if necessary. Owing to the chronic nature of OAB, the ideal anticholinergic treatment should have good long-term efficacy and tolerability. There are many anticholinergics available, although some of these are not specific for the bladder and can cause adverse effects such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
2

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 31 publications
0
11
0
2
Order By: Relevance
“…To confirm the efficacy of a particular drug, a study should determine whether the therapeutic agent is superior to a placebo and whether it is also not inferior to a pre‐existing drug. However, imidafenacin has already been reported to have significantly higher efficacy than placebos in both phase 2 and 3 trials,and these findings have been well‐reviewed …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To confirm the efficacy of a particular drug, a study should determine whether the therapeutic agent is superior to a placebo and whether it is also not inferior to a pre‐existing drug. However, imidafenacin has already been reported to have significantly higher efficacy than placebos in both phase 2 and 3 trials,and these findings have been well‐reviewed …”
Section: Discussionmentioning
confidence: 99%
“…However, imidafenacin has already been reported to have significantly higher efficacy than placebos in both phase 2 and 3 trials, 4,5 and these findings have been well-reviewed. 27 -29…”
Section: Discussionmentioning
confidence: 99%
“…Since imidafenacin exhibited greater selectivity for the M 3 than M 2 subtype in CHO-K1 cells expressing human muscarinic receptors (4), the high affinity of [ 3 H]imidafenacin for muscarinic receptors in the human parotid gland reflects M 3 -subtype selectivity. In vivo functional and ex vivo muscarinic receptor binding experiments in rats (5,6) and clinical studies in humans (9,10) showed that imidafenacin selected the bladder over the exocrine gland. These in vivo results appear to contradict the M 3 -subtype selectivity observed in vitro, but in vivo bladder selectivity has been mainly attributed to the pharmacokinetic property of this agent (6).…”
Section: Discussionmentioning
confidence: 99%
“…Imidafenacin is known to be a well-tolerated agent in clinical settings and causes fewer adverse effects (7,8). Masumori (9), Takeuchi et al (10), and Maggiore et al (11) recently reviewed the long-term efficacy, safety, and tolerability of imidafenacin and reported a reduced incidence of severe adverse events such as dry mouth and constipation. In addition, imidafenacin can be used safely for a long period of time even by cognitively vulnerable elderly patients with the symptoms of OAB.…”
mentioning
confidence: 99%
“…In the current study, we used type 2 diabetes mellitus rats as a model of cold stress‐exacerbated LUTS in diabetes patients. Muscarinic receptor antagonists are considered as the first‐line drug to treat OAB syndrome . We determined if the muscarinic receptor antagonist, imidafenacin, could inhibit the cold stress‐induced detrusor overactivity in non‐diabetic and diabetic rats.…”
Section: Introductionmentioning
confidence: 99%